Islamic Studies di Indonesia (Pendekatan Fenomenologi) - Yuni Masrifatin; Muh Barid Nizarudin Wajdi (Proceedings of Annual Conference for Muslim Scholars, 2018)
Most Islamic education rarely focus on affective and psychomotor domain. Whereas, education is a learning process in order to student can develop their potential capabilities to get spiritual, Emotional control, self control, personality, intelligence, good character and skill. With phenomenological approach, Islamic education should focus on consciousness process or magical consciousness, naive consciousness and critical consciousness, humanity and good character building